Florence "blues" are clothed in triple basic terms. (September 2022) - Del Viva, Maria Michela; Mariani, Ilaria; Caro, Carmen De; Paramei, Galina V.
Psycholinguistic studies provide evidence that Italian has more than one basic color term (BCT) for "blue": consensually, blu denotes "dark blue, " while "light-and-medium blue, " with diatopic variation, is termed either azzurro or celeste . For Tuscan speakers (predominantly from Florence), the BLUE area is argued to linguistically differentiate between azzurro "medium blue" and celeste "light blue." We scrutinized "basicness" of the three terms. Participants ( N = 31; university students/graduates born in Tuscany) named each chip of eight Munsell charts encompassing the BLUE area (5BG-5PB; N = 237) using an unconstrained color-naming method. They then indicated the "best exemplar" (focal color) of blu, azzurro and celeste . We found that frequencies of the three terms and of term derivatives were comparable. Referential meaning of blu, azzurro, and celeste was estimated in CIELAB space as L*a*b*- coordinates of the mean of focal colors and as "modal" categories, that is, dispersion around the mean. The three "blue" terms were distinct on both measures and separated along all three CIELAB dimensions but predominantly along the L* -dimension. Our results provide evidence that Tuscan speakers require all three terms for naming the BLUE area, categorically refined along the lightness dimension. Furthermore, celeste appears to be a third BCT for "blue, " along with commonly considered BCTs azzurro and blu . The "triple blues" as BCTs for Tuscan speakers are in contrast with outcomes of two "blue" basic terms estimated by using the same methodology in two other locations in Italy— azzurro and blu (Verona, Veneto region) or celeste and blu (Alghero, Sardinia).